An Ambient Assisted Living Approach in Designing Domiciliary Services Combined With Innovative Technologies for Patients With Alzheimer's Disease: A Case Study. (February 2015) - Cavallo, Filippo; Aquilano, Michela; Arvati, Marco
Background: Alzheimer's disease (AD) is one of the most disabling diseases to affect large numbers of elderly people worldwide. Because of the characteristics of this disease, patients with AD require daily assistance from service providers both in nursing homes and at home. Domiciliary assistance has been demonstrated to be cost effective and efficient in the first phase of the disease, helping to slow down the course of the illness, improve the quality of life and care, and extend independence for patients and caregivers. In this context, the aim of this work is to demonstrate the technical effectiveness and acceptability of an innovative domiciliary smart sensor system for providing domiciliary assistance to patients with AD which has been developed with an Ambient Assisted Living (AAL) approach. Methods: The design, development, testing, and evaluation of the innovative technological solution were performed by a multidisciplinary team. In all, 15 sociomedical operators and 14 patients with AD were directly involved in defining the end-users' needs and requirements, identifying design principles with acceptability and usability features and evaluating the technological solutions before and after the real experimentation. Results: A modular technological system was produced to help caregivers continuously monitor the health status, safety, and daily activities of patients with AD. During the experimentation, the acceptability, utility, usability, and efficacy of this system were evaluated as quite positive. Conclusion: The experience described in this article demonstrated that AAL technologies are feasible and effective nowadays and can be actively used in assisting patients with AD in their homes. The extensive involvement of caregivers in the experimentation allowed to assess that there is, through the use of the technological system, a proven improvement in care performance and efficiency of care provision by both formal and informal caregivers and consequently an increase in the quality of life of patients, their relatives, and their caregivers.